2019
DOI: 10.1038/s41598-019-50095-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetes and Keratoconus: A Retrospective Analysis

Abstract: Keratoconus (KC) and chronic diabetes mellitus (DM) are both associated with significant defects in the human corneal structure. Studies have long suggested that DM is linked to KC, mainly via the crosslinking mechanism, but scientific evidences are lacking. The role of altered systemic metabolism is well-established in both DM and KC with studies suggesting localized altered cellular metabolism leading to the development of corneal pathologies. We have previously characterized the metabolic defects associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…One method is to supplement culture media with ascorbic acid (vitamin C), which normally promotes collagen secretion and deposition without promoting myofibroblast differentiation [ 5 , 16 , 33 , 34 , 47 , 81 , 82 ]. This hCF stroma-like 3D model and their self-assembled matrix, which mimics the corneal stroma during development [ 33 , 47 , 83 ], but also useful in investigating other pathologies affecting the corneal stroma, such as keratoconus [ 84 , 85 , 86 ], wound healing [ 33 , 87 ], and diabetes [ 88 , 89 , 90 ]. Collectively, these studies highlight that by increasing ECM dimensionality around hCFs, which can significantly influence cell proliferation and survival, mechano-responses, and their differentiation capacity [ 33 , 47 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…One method is to supplement culture media with ascorbic acid (vitamin C), which normally promotes collagen secretion and deposition without promoting myofibroblast differentiation [ 5 , 16 , 33 , 34 , 47 , 81 , 82 ]. This hCF stroma-like 3D model and their self-assembled matrix, which mimics the corneal stroma during development [ 33 , 47 , 83 ], but also useful in investigating other pathologies affecting the corneal stroma, such as keratoconus [ 84 , 85 , 86 ], wound healing [ 33 , 87 ], and diabetes [ 88 , 89 , 90 ]. Collectively, these studies highlight that by increasing ECM dimensionality around hCFs, which can significantly influence cell proliferation and survival, mechano-responses, and their differentiation capacity [ 33 , 47 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The corneal stroma is also known to be affected, in diabetic keratopathy, although studies are lacking [ 46 , 47 ]. The process of stromal wound healing involves wound contracture, bringing the margins of open wounds together [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis and gluconeogenesis are two metabolic pathways involved in glucose catabolism and anabolism, respectively, which play a key role in cell survival [117,118]. Studies performed on in vitro models of KC demonstrated that glucose metabolism is upregulated [119][120][121]. In particular, anaerobic glycolysis appears to be the most affected, since concentrations of lactate are higher than pyruvate [102].…”
Section: Glycolysis and Gluconeogenesismentioning
confidence: 99%
“…Findings on glucose metabolism alterations led to the investigation of a possible role of diabetes mellitus (DM) in KC pathogenesis. However, results obtained from different studies were controversial, and clinical data suggest that DM is a protective rather than a risk factor for KC onset and progression [121,124].…”
Section: Glycolysis and Gluconeogenesismentioning
confidence: 99%